2021
DOI: 10.3389/fonc.2021.630241
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: LncRNA SNHG19 Promotes the Development of Non-Small Cell Lung Cancer via Mediating miR-137/E2F7 Axis

Abstract: ObjectiveNon-small cell lung cancer (NSCLC) is a common malignant tumor, which has high incidence and low the 5-year survival rate. Long non-coding RNAs (lncRNAs) play critical roles in carcinoma occurrence and metastasis. Herein, our aim was to investigate the effects of lncRNA SNHG19 in NSCLC progression.Materials and MethodsLong non-coding RNA Small Nucleolar RNA Host Gene 19 (lncRNA SNHG19) expression level was measured by bioinformatics and qRT-PCR. Edu, Transwell, and scratch assays were performed to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“… 24 E2F7 was highly expressed in LUAD tissues and involved in the progression of NSCLC through regulating LncRNA-SNHG19. 25 E2F7 also played an important role in the Circ-AASDH/miR-140-3p/E2F7 axis and participated in regulating LUAD tumor growth. 26 A recent study reported that E2F8 expression was found to be significantly upregulated in lung cancer tissues and cells by immunofluorescence staining, and knockdown E2F8 could inhibit lung cancer cell proliferation and tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“… 24 E2F7 was highly expressed in LUAD tissues and involved in the progression of NSCLC through regulating LncRNA-SNHG19. 25 E2F7 also played an important role in the Circ-AASDH/miR-140-3p/E2F7 axis and participated in regulating LUAD tumor growth. 26 A recent study reported that E2F8 expression was found to be significantly upregulated in lung cancer tissues and cells by immunofluorescence staining, and knockdown E2F8 could inhibit lung cancer cell proliferation and tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 Many special lncRNAs have been proven to be abnormally expressed and used as specific molecular markers in many human tumors. 23 , 24 SNHG16, a non-coding RNA expressed in aggressive neuroblastoma, is 2435 nucleotides long and located on chromosome 17q25.1. 13 , 25 In recent years, the role of SNHG16 in malignant tumors has been widely studied.…”
Section: Discussionmentioning
confidence: 99%